English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

i am horrible at algebra(i need the work to be shown here please)

2006-10-14 17:21:12 · 19 answers · asked by George W 1 in Science & Mathematics Mathematics

19 answers

u=29

32u - 8 -12u = 22u -66
20u -8 = 22u -66
-8 = 2u -66
-8+66 = 2u
2u = 58
u = 58/2 =29

2006-10-14 17:28:31 · answer #1 · answered by Jimbo 5 · 3 0

Here's how to do it.

You see the paranthesis? You need to remove them first. To do so, take the number in front of the paranthesis and multiply the inside by it. For example:

8(4u - 1) becomes 32u - 8

Do this on both sides, and the equation will become as follows:

32u - 8 - 12u = 22u - 66

Then, you need to move "like terms" on each side. Like terms are, numbers with U at the end, and just the numbers.

Remember, when you move anything ACROSS the equal sign, the sign changes. + becomes - and - becomes +.

When you do this, the formula changes from:
32u - 8 - 12u = 22u - 66

to:
32u - 12u - 22u = -66 + 8

Notice, when number was moved across, the sign in front of it came with the number and chagned signs.

Now, you just have to do the math...
32u - 12u - 22u becomes -2u
-66 + 8 becomes -58

Now the equation is -2u = -58

Divide the both sides by -2 and you get:
u = 29
which is a final answer.

2006-10-14 17:34:44 · answer #2 · answered by tkquestion 7 · 1 0

Parenthesis. Exponents. Multiplication. Division. Addition. Subtraction. or also known as P.E.M.D.A.S

**step1: when using parenthesis it means multiply so lets multiply

8(4u - 1) -12u = 11(2u - 6)
---------------------------------------
32u - 8 - 12u = 22u - 66

**step 2: transpose the similar variables on one side and on the other (when transposing, remember to change the sign from positive to negative and vice versa)

32u - 8 - 12u = 22u - 66
---------------------------------------
32u - 12u - 22u = -66 + 8

**step 3: add or subtract whatever value

32u - 12u - 22u = -66 + 8
---------------------------------------
20u - 22u = -58
---------------------------------------
-2u = -58

**step 4: there are never any negative variables so multiply this by -1

(-2u = -58) -1
---------------------------------------
2u = 58

**step 5: divide this by 2 since it says "2u = 58"

2u / 2 = 58 / 2
---------------------------------------
u = 29

**step 6: check if you have the right answer by substituting

8[4(29) - 1] -12(29)=11[2(29) - 6]
---------------------------------------
8 (116 - 1) - 348 = 11(58 - 6)
---------------------------------------
8 (115) - 348 = 11(52)
---------------------------------------
920 - 348 = 572
---------------------------------------
572 = 572 >>>>>>CORRECT!!!

2006-10-14 19:03:04 · answer #3 · answered by Princess Answers 3 · 0 0

8(4u-1)-12u=11(2u-6)
First, distribute the 8 and 11
32u-8-12u=22u-66
Then subtract 12u from 32u
20u-8=22u-66
Next, add 66 to -8 and subtract 20u from 22u
58=2u
Divide 58 by 2
29=u

2006-10-14 17:31:52 · answer #4 · answered by Anonymous · 3 0

8(4u - 1) - 12u = 11(2u - 6)
(8x4u) - (8x1) - 12u = (11 x 2u) - (11 x 6)
32u - 8 -12u = 22u - 66
32u - 12u - 8 = 22u - 66
20u - 8 = 22u - 66
20u - 22u = -66 + 8
-2u = - 58
-u = -29
u = 29

2006-10-14 18:09:34 · answer #5 · answered by TheresaE 2 · 1 0

8(4u-1)-11(2u-6)=12u
32-8-22u+66=12u
10u+58=12u
10u-12u=-58
(-2u=-58) / -2
u= 29

crap, im not that good as well in algebra but i did my best to answer that one, and ye i had fun,..thnks

2006-10-14 17:42:22 · answer #6 · answered by Anonymous · 1 0

8(4u-1)-12u=11(2u-6)
32u-8-12u=22u-66
32u-12u-22u=-66+8
20u-22u=-58
-u=-58
u=58(cancel - on both sides)

2006-10-14 20:16:07 · answer #7 · answered by srirad 2 · 0 0

Closed ( up ) u made a mistake just before the last row 66-8=58 the correct answer is u=29

2006-10-14 17:32:11 · answer #8 · answered by Sora 6 · 2 0

use distributive property.
so the equation transforms to

32u-8-12u=22u-66

combine like terms.

20u-8=22u-66

subtract/add from one side of the equation applies to the other side.

-2u-8=-66
-2u=-58

divide both sides to isolate u.
u= 29.
negative divided by negative is positive and applies to negative to negative too.

2006-10-14 17:32:05 · answer #9 · answered by :)<3 3 · 2 0

you basically use the main distribution process

8(4u-1)-12u=11(2u-6)
32u-8-12u=22u-66
20u-8=22u-66
58=2u
29=u

Hope I helped!
Email me if you have any other questions...it should be on my profile.
~SmS~

2006-10-14 21:29:48 · answer #10 · answered by ♥Pyar Ki Pari♥ 4 · 0 0

fedest.com, questions and answers